Genetic analysis and genome-wide association mapping of carotenoid and dry matter content in cassava - Esuma, Williams (University of the Free State, 2016)
Global efforts are underway to develop staple crops with improved levels of provitamin A carotenoids to help combat dietary vitamin A deficiency (VAD), which has afflicted the health of resource-poor farmers in the developing world. As a staple crop for more than 500 million people in sub-Saharan Africa, cassava (Manihot esculenta Crantz) enriched with provitamin A carotenoids could have a widespread nutritional impact. In Uganda, cassava is the second most consumed crop after bananas. Accordingly, the national cassava programme initiated a breeding pipeline to develop cassava genetic resources combining high carotenoid content with farmer-preferred traits. To advance this initiative, a study was conducted with specific objectives to (1) determine the combining ability of provitamin A genotypes and gene actions in inheritance of carotenoid content and dry matter content (DMC) in cassava, (2) assess the effect of genotype by environment interaction (GEI) on accumulation of carotenoid content and DMC in cassava roots and (3) identify genomic regions and polymorphisms linked to natural variation for carotenoid content and DMC in cassava. A 6x6 partial diallel analysis was conducted to estimate combining ability of six provitamin A clones and gene actions controlling carotenoid content and DMC in cassava roots. Fifteen F1 families generated from diallel crosses were evaluated in two environments in Uganda. General combining ability (GCA) effects were significant for total carotenoid content (TCC) and DMC, suggesting the relative importance of additive gene effects in controlling these traits in cassava. Genotype MH02-073HS was the best general combiner for TCC and fresh root weight (FRW) while NASE 3 was the best general combiner for DMC. Such genotypes with desirable GCA effects could form the genetic basis for breeding programmes targeting improvement of cassava for TCC and DMC. Importantly, 64 genotypes were selected from the 15 F1 families for advancement because of their superior performance for TCC, DMC and FRW. When GEI effects for carotenoid content and DMC were assessed by evaluating 13 advanced provitamin A clones in six environments, additive main effect and multiplicative interaction analysis showed significant variation among genotypes for TCC, FRW and DMC. Environmental effects were non-significant for TCC, but GEI effects were significant for all these traits. From this effort, best performing genotypes were identified for TCC, DMC and FRW and could constitute the genetic material for on-farm testing or further recombination through systematic hybridisation programmes. To survey genetic factors associated with carotenoid content in cassava, a high throughput genotyping-by-sequencing platform was used to genotype a panel of 591 genotypes using 635 247 single nucleotide polymorphisms (SNPs) distributed across the cassava genome. Through marker-trait association testing, a genomic region stretching 1.37 Mb on chromosome 1 was identified to contain seven SNPs significantly associated with carotenoid content in cassava. A survey of the cassava genome sequence v6.1 positioned these SNPs in the vicinity of Manes.01G124200.1, a gene known to increase carotenoid concentration in cassava roots. These findings demonstrated the usefulness of GWAS for dissecting the genetic architecture of traits in cassava and could offer practical grounds for improving carotenoid content in cassava through MAS and genomic selection. Overall, a significant negative correlation was found between TCC and DMC, indicating the need for breeders to adopt methods that can combine high levels of these traits, given farmers prefer high DMC. Nonetheless, the study suggested an opportunity for cassava biofortification in eastern Africa. Improved genotypes were identified and genetic information generated, which could form the primary resources for systematic development of carotene-rich cassava varieties for deployment to farmers. Consumption of such nutritious varieties would sustainably reduce VAD among resource-poor peasants, for the benefit of their own physical and economic development.

Globale pogings is onderweg om stapelgewasse te ontwikkel met verbeterde vlakke van provitamien A karotenoïede om te help met die stryd teen dieet gebasseerde vitamien A tekorte (VAD), wat die gesondheid van hulpbron arm boere in die ontwikkelende wêreld affekteer. As ‘n stapelgewas vir meer as 500 miljoen mense in sub-Sahara Afrika, kan cassava (Manihot esculenta Crantz), verreik met provitamien A karotenoïede, ‘n wye voedings impak hê. In Uganda is cassava die tweede mees belangrike stapelgewas na piesangs. Daarom het die nasionale cassava program ‘n telingspyplyn begin om cassava genetiese hulpbronne te ontwikkel wat hoë karotenoïed inhoud kombineer met eienskappe wat deur boere verkies word. Om hierdie inisiatief te bevorder, is hierdie studie uitgevoer met die spesifieke doel om (1) die kombineervermoë van provitamien A in genotipes, en geenaksies in oorwerwing van karotenoïed inhoud en droëmassa inhoud (DMC) te bepaal in cassava (2) om die effek van genotipe by omgewing interaksie (GEI) op die akkumulasie van karotenoïed inhoud en DMC in cassava wortels te bepaal en (3) om die genomiese streke en polimorfismes gekoppel aan natuurlike variasie vir karotenoïed inhoud en DMC in cassava te bepaal. ‘n 6x6 gedeeltelike dialleel analise is gedoen om die kombineervermoë van ses provitamien A klone en geenaksies van karotenoïed inhoud en DMC inhoud in cassava wortels te bepaal. Vyftien F1 families, gegenereer van die dialleel kruisings, is geëvalueer in twee omgewings in Uganda. Algemene kombineervemoë (GCA) effekte was betekenisvol vir totale karotenoïed inhoud (TCC) en DMC, wat die relatiewe belangrikheid van additiewe geeneffekte aandui in die beheer van hierdie eienskappe in cassava. Genotipe MH02-073HS was die beste algemene kombineerder vir TCC en vars wortel gewig (FRW) terwyl NASE 3 die beste algemene kombineerder was vir DMC. Sulke genotipes met gunstige GCA effekte kan die genetiese basis vorm vir teelprogramme vir die verbetering van cassava vir TCC en DMC. Belangrik is dat 64 genotipes geselekteer is van die 15 F1 families vir verdere ontwikkeling op grond van hulle goeie TCC, DMC en FRW eienskappe. Die GEI effekte vir karotenoïed inhoud en DMC is bepaal met die evaluasie van 13 gevorderde provitamien A klone in ses omgewings. Additiewe hoofeffek en multiplikatiewe interaksie analise het betekenivollve variasie tussen genotipes getoon vir TCC, FRW en DMC. Omgewingseffekte was nie betekenisvol vir TCC nie, maar GEI effekte was betekenisvol vir al hierdie eienskappe. Uit hierdie analise is die beste genotipes geïdentifiseer vir TCC, DMC en FRW en hulle kan die genetiese basis vorm vir evaluasie op die plase of vir verdere rekombinasie deur sistematiese hibridisasie programme. Om die genetiese faktore geassosieer met karotenoïed inhoud in cassava te bepaal, is ‘n hoë deurvloei genotipering-by-volgordebepalings platform gebruik om ‘n paneel van 591 genotipes te genotipeer met 635 247 enkel nukleotied polimorfismes (SNPs) versprei oor die cassava genoom. Deur merker-eienskap assosiasie toetse, is ‘n genoom area oor 1.37 Mb op chromosoom 1 geïdentifiseer met sewe SNPs wat betekenisvol met karotenoïed inhoud in cassava geassosieer is. ‘n Opname van die cassava genoom volgorde v6.1 het hierdie SNPs in die omgewing van Manes.01G124200.1, ‘n geen bekend vir die verhoging van karotenoïed konsentrasie in cassava wortels, geplaas. Hierdie bevindings het die bruikbaarheid van GWAS bewys vir die bepaling van genetiese argitektuur van eienskappe in cassava en kan ‘n praktiese basis vorm vir die verbetering van karotenoïed inhoud in cassava deur MAS en genomiese seleksie. In die algeheel gesien is ‘n negatiewe korrelasie gevind tussen TCC en DMC, wat die nodigheid wys vir telers om metodes te gebruik wat hoë vlakke van hierdie eienskappe kombineer, omdat boere hoë DMC verkies. Nietemin het die studie die moontlikheid van cassava biofortifikasie in oos Africa uitgewys. Verbeterde genotipes is geïndentifiseer en genetiese inligting is gegenereer wat die primêre hulpbron kan vorm vir sistematiese ontwikkeling van karotenoïed-ryk cassava variëteite vir verspreiding aan boere. Die inname van sulke voedingryke variëteite kan lei tot volhoubare vermindering van VAD onder hulpbron arm boere, wat tot die voordeel van hulle eie fisiese en ekonomiese ontwikkeling sal wees.
Thesis (Ph.D. (Plant Sciences (Plant Breeding))--University of the Free State, 2016
Keywords: Biofortification; Cassava; Combining ability; Genetic improvement; GWAS; Provitamin A carotenoid; Stability; Vitamin A deficiency; Carotenoids; Cassava -- Genetics